A study to assess Ill effects of prolonged use of mobile phones among nursing students of college of nursing, pravara institute of medical sciences (D.U.), Loni Bk - Belokar, Jitendra D. (Innovational: Journal of Nursing and Healthcare, 2024)
Mobile phones have been of tremendous assistance to all of us. The adaptation of mobile phone by young people has been global phenomenon in recent years. It has now an integral part of our daily lives. Concerns continue to be raised about potential ill health impacts associated with the mobile phone use. Hence this study was undertaken to assess ill effects of prolonged use of mobile phones. Objectives: 1. to assess physiological ill effects of prolonged use of mobile phones 2. To assess psychological ill effects of prolonged use of mobile phones, among nursing students of College of Nursing, PIMS, Loni. Methodology: Descriptive study design with cross sectional survey approach was used. 60 subjects were selected with stratified random sampling technique. Data was collected by using structured questionnaire which was designed to assess physiological and psychological ill effects of prolonged use of mobile phones. Data was analyzed by using descriptive statistics such as frequency and percentage. The level of physiological and psychological ill effects of prolonged use of mobile phone was classified as mild, moderate and severe. Findings: Findings of present study revealed that 62.66% participants had mild physiological ill effects, 32% subjects had moderate and 6% participants had severe physiological ill effects due to prolonged use of mobile phones. Also study revealed that 46.66% participants had mild psychological ill effects and 53.33% participants had moderate psychological ill effects due to prolonged use of mobile phones. Conclusion: Use of mobile phone for longer period can lead to mild to severe ill effects